Integrated Rural Development: Sebuah Tinjauan Literatur Sistematis di Indonesia - Dewi Rizkwanti, Robertha Astri Karunia; Kurniawan, Andreas Redi (Jurnal Ilmiah Administrasi Publik, 2025)
This article aims to discuss how Village Development in Indonesia takes an integrated rural development approach. We use a Systematic Literature Review (SLR) to explore how research uses IRD in Village development in Indonesia and identify areas for further research. The steps based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analysis) method because it is capable of providing a structured procedure in the SLR approach. The PRISMA method is used to help search for various literature, as well as identify inclusion and exclusion criteria for selecting literature material. This study found that several studies used this approach in 8 (eight) areas which include agricultural development, infrastructure development, sustainable livestock development, community empowerment, settlement development, resource development, deliberation and tourism development. IRD is used as a tool to reconfigure Village Development by taking into account social capital, culture, the environment and local knowledge. IRD was oriented towards community welfare and the principles of justice.  IRD strives to increase productivity, infrastructure income and social development in rural areas. Therefore, the important element in this concept is the involvement of local communities in development. IRD is comprehensive and based on a system that places production and social components in a balanced position. This study identifies several areas that have not been covered in the implementation of IRD and, which are considered to be its limitations, such as its relationship to innovation and knowledge of local communities and how these things influence Village Development and demographic factors